2014
DOI: 10.3109/19396368.2014.915360
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondrial aconitate (ACO2) in human sperm motility

Abstract: Deficiencies in tricarboxylic acid (TCA) cycle enzymes have been shown to cause a wide spectrum of human diseases, including malignancies and neurological and cardiac diseases. In mammalian spermatozoa mitochondria, the TCA cycle is known to be a crucial metabolic pathway that contributes to produce ATP. There is little known about the role and mechanism of mitochondrial aconitase (ACO2), which is an important regulatory enzyme of the TCA cycle, in asthenozoospermia. In the current study, immunofluorescence st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…YBX1, which is also known as Y-box transcription factor, is involved in spermatogenesis [15,16]. Mitochondrial ACO2 and AK1 are required for sperm motility [13,17]. Consistent with the proteomic 2; Supplementary Table 1), the upregulation of YBX1 and downregulation of ACO2 and AK1 in sperm from the ICSI group were experimentally validated (Fig.…”
Section: Differentially Expressed Proteins Identified In the Sperm Of Infertile Males Who Received Icsisupporting
confidence: 52%
See 1 more Smart Citation
“…YBX1, which is also known as Y-box transcription factor, is involved in spermatogenesis [15,16]. Mitochondrial ACO2 and AK1 are required for sperm motility [13,17]. Consistent with the proteomic 2; Supplementary Table 1), the upregulation of YBX1 and downregulation of ACO2 and AK1 in sperm from the ICSI group were experimentally validated (Fig.…”
Section: Differentially Expressed Proteins Identified In the Sperm Of Infertile Males Who Received Icsisupporting
confidence: 52%
“…Based on the abovementioned results and previous studies [13][14][15][16], we selected three significantly differentially expressed proteins, including ACO2, AK1, and YBX1, for further validation. These proteins are essential for sperm motility and spermatogenesis.…”
Section: Differentially Expressed Proteins Identified In the Sperm Of Infertile Males Who Received Icsimentioning
confidence: 99%
“…ACO2 is an enzyme involved in the second step of the TCA cycle, that catalyzes the interconversion of citrate to isocitrate. Little is known about the role and mechanism of ACO2 in asthenozoospermia, although immunoblotting experiments demonstrated that the level of ACO2 protein in the asthenozoospermic samples was significantly decreased in comparison to normal fertile men [21]. It is interesting to underline that mitochondrial aconitase activity could be considered a functional indicator of mitochondrial levels of reactive oxygen species (ROS), because the iron-sulfur core of this enzyme is oxidized by superoxide anions, reducing its activity [22].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that ACO2 protein increased by 60% in ISCA1 knockout embryos (Figure A,C), unlike the observed decrease in Fe/S transfer protein. ACO2 is central to carbohydrate and energy metabolism and is associated with multiple metabolic pathways and pathologic conditions such as Huntington's Disease, hypoxia, and reactive oxygen species (ROS) and energy metabolism defects . ACO2 production could be regulated by cell energy metabolism and the observed increase in ACO2 activity might counteract cell energy metabolism defects .…”
Section: Discussionmentioning
confidence: 99%
“…ACO2 is central to carbohydrate and energy metabolism and is associated with multiple metabolic pathways and pathologic conditions such as Huntington's Disease, hypoxia, and reactive oxygen species (ROS) and energy metabolism defects . ACO2 production could be regulated by cell energy metabolism and the observed increase in ACO2 activity might counteract cell energy metabolism defects . We speculated that the ISCA1 knockout resulted in damage to the mitochondrial respiratory chain complex I via a decrease in NDUFA9 protein, leading to defective energy metabolism.…”
Section: Discussionmentioning
confidence: 99%